The Huguenots of Paris and the coming of religious freedom, 1685-1789 - Garrioch, David (Cambridge University Press, 2014)
How did the Huguenots of Paris survive, and even prosper, in the eighteenth century when the majority Catholic population was notorious for its hostility to Protestantism? Why, by the end of the Old Regime, did public opinion overwhelmingly favour giving Huguenots greater rights? This study of the growth of religious toleration in Paris traces the specific history of the Huguenots after Louis XIV revoked the Edict of Nantes in 1685. David Garrioch identifies the roots of this transformation of attitudes towards the minority Huguenot population in their own methods of resistance to persecution and pragmatic government responses to it, as well as in the particular environment of Paris. Above all, this book identifies the extraordinary shift in Catholic religious culture that took place over the century as a significant cause of change, set against the backdrop of cultural and intellectual transformation that we call the Enlightenment--